Вплив тютюнопаління на показники рівня фізичного стану та тип гемодинаміки в осіб жіночої статі - Апончук, Людмила; Шевчук, Тетяна; Бернацька, Ніна; Aponchuk, Liudmyla; Shevchuk, Tetiana; Bernaska, Nina (Східноєвропейський національний університет імені Лесі Українки, 2014)
Активне куріння негативно впливає на показники серцево-судинної системи та рівень фізичного стану осіб жіночої статі. Показники рівня фізичного стану є достовірно вищими у жінок, які курять, порівняно з жінками-некурцями. Про це свідчить збільшення показників частоти серцевих скорочень, артеріального тиску та неконтрольованої маси тіла. Основні показники центральної гемодинаміки, такі як ЧСС, СДТ, СІ, в осіб жіночої статі, які курять, достовірно вищі порівняно з жінками-некурцями. The objective of the research was to investigate the influence tobacco smoking on the indices of physical condition level and type of hemodynamics in female individuals. 30 female individuals between 21 and 35 years of age (mature age, І period) were examined. The participants were divided into two groups: 15 female smokers that consume tobacco smoke for 2−5 years and 15 female non-smokers (control group). The level of physical development was evaluated using regression equation (where X − quantitative index, equal to the level of estimated physical condition). The indices and type of central hemodynamics were measured using the method of tetrapolar rheography (Kubichenko’s rheography method). Some peculiarities were defined during the research. Physical condition level is reliably higher in women that consume tobacco smoke, than in female non-smokers. This assumption is based on the increase of indices of cardiac rhythm, blood pressure, and uncontrolled body weight, which appears as a result of metabolic disorder, accelerated heartbeat, embolism caused by negative impact of tobacco smoke constituents. Such indices of central hemodynamics as heart rate, systolic and diastolic blood pressure, cardiac index, in women that smoke are reliably higher than in those that do not. This characteristics shows that blood pressure increases to 20−30 %, cardiac rate and output raises, vasoconstriction of the peripheral arteries occur, and blood circulation decreases there for 40−45 % because of systematic smoking. The research on types of hemodynamics showed that active smokers (2−5 years) belong more to hiperdynamic type, while non-smokers (control group) constitute more the hipodynamic type. This difference is caused by the increase of major hemodynamic indices and accelerated cardiac performance that occurred due to the influence of sympathetic nervous system.
The Influence of Tobacco Smoking on the Indices of Physical Condition Level and Type of Hemodynamics in Female Individuals
Keywords: гемодинаміка; фізичний стан; тютюнопаління; жіночий організм; hemodynamics; physical condition; tobacco smoking; female organism